AERODYNAMIC CHARACTERISTICS OF AIRFOIL USING PANEL METHOD - Buyung Junaidin (Institut Teknologi Dirgantara Adisutjipto, 2017)
Potential flow over an airfoil plays an important historical role in the theory of flight. The governing equation for potential flow is Laplace’s equation, a widely studied linear partial differential equation. One of Green’s identities can be used to write a solution to Laplace’s equation as a boundary integral. Numerical models based on this approach are known as panel methods in the aerodynamics community. This paper introduces the availability of a computational tool for constructing numerical modelfor potential flow over an airfoil based on panel methods. Use of the software is illustrated by implementing a specific model using Hess and Smith panel method to compute the flow over a member of the NACA four-digit airfoils.